Penyesuaian Diri Mahasiswa yang Tinggal di Asrama Yayasan Amal Saleh - Duri, Rapika; Zikra, Zikra (Consilium, 2021)
There is a phenomenon of students experiencing problems adjusting to students in the Amal Saleh Foundation dormitory. The influencing factors are environmental factors such as students who have not been able to build social relationships with other students, students who have not been able to accept regulations, students who have not been able to hold back their emotions when faced with problems. When this happens it will affect the student's self-adjustment so that students prefer to leave the dormitory. This research aims to find out and describe the adjustment of students living in the Amal Saleh Foundation hostel. The data collection was a Likert scale model questionnaire.The results showed that (1) overall student self-adjustment was in the moderate category with a percentage of 48.7%, (2) student self-adjustment seen from the presence of emotions that were not excessive was in the low category with a percentage 41.4%, (3) student self-adjustment seen from self-defense mechanisms which is at least in the low category with a percentage of 38.6%, (4) student self-adjustment seen from feelings of personal frustration which is at least in the low category with a percentage of 44, 3%. (5) self-adjustment seen from rational considerations and the ability to direct oneself is in the moderate category with a percentage of 27.1% (6) self-adjustment: students seen from the ability to learn and utilize past experience are in the moderate category with a percentage of 32.9% ( 7) student self-adjustment seen from a realistic and objective attitude is in the medium category with a percentage of 35.7%